2006
DOI: 10.1111/j.1365-263x.2006.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the effectiveness of a one‐step conditioning agent in sealant placement: 6‐month results

Abstract: In view of the findings of this investigation, best practice for the placement of sealants remains enamel preparation with acid etch and the use of an intermediate bonding layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Sealants were assessed according to a modified version of the CCC sealants evaluation system described by Deery et al 8,9 For each child, assessment scores were recorded using a proforma that included basic demographic information. Data obtained was subjected to statistical analysis using the Z-test for proportion using SPSS software 19 using Windows.…”
Section: Methodsmentioning
confidence: 99%
“…Sealants were assessed according to a modified version of the CCC sealants evaluation system described by Deery et al 8,9 For each child, assessment scores were recorded using a proforma that included basic demographic information. Data obtained was subjected to statistical analysis using the Z-test for proportion using SPSS software 19 using Windows.…”
Section: Methodsmentioning
confidence: 99%
“…31 Sealant placement with self-etch adhesives was found to have poor retention when compared to those sealants placed with phosphoric acid etching. Similar to the current study, Burbridge and others 32 compared the retention of fissure sealants placed on occlusal surfaces following the use of a self-etching priming agent and traditional acid etch. While Xeno III (Dentsply International, York, PA, USA) was used to prepare the occlusal enamel on one side of the lower arch, phosphoric acid, together with Prime & Bond (Dentply Caulk, Milford, DE, USA), was used on the other side.…”
Section: Discussionmentioning
confidence: 72%
“…This confirms previous 12-month clinical studies evaluating occlusal sealant retention. 25,26 Because occlusal sealants that fill pits and fissures are thicker than facial sealants, more surface resin can be lost without losing coverage of the tooth. While thickness may explain why retention is lower in facial sealants, viscosity and oxygen inhibition must also be considered in order to explain the differences between the ETCH and SEP groups.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no difference in the bond strength of orthodontic brackets between traditional etching and SEP, 23,24 it is reasonable to assume that SEP could be used effectively with facial sealants placed before bonding brackets. While lower retention of occlusal sealants has been reported for SEP than for ETCH, 25,26 a 24-month clinical trial found no difference in retention between the two etching protocols. 27 It has also been shown that SEP provides less resistance to decalcification than does traditional etching.…”
Section: Introductionmentioning
confidence: 99%